(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Gambling disorder is characterized by persistent loss of control over gambling behavior, generating individual, social, and economic impacts. This systematic review evaluated the effectiveness of biopsychosocial interventions targeting gambling-related behaviors, with emphasis on implications for public policy. A search was conducted in Scopus for studies published between 2019 and 2024, following the PICOS framework and PRISMA protocol. Twenty-six randomized controlled trials were included and classified as psychological (n = 17), behavioral/environmental (n = 6), or medicinal interventions (n = 3). Cognitive-behavioral therapy showed the strongest evidence of effectiveness, with additional benefits in group-based modalities, including increased treatment retention. Online interventions emerged as a viable strategy to expand access. Self-regulation strategies demonstrated positive outcomes. Medicinal interventions showed potential but were limited by small samples. Responsible gambling messages did not demonstrate effectiveness. More segmented studies and robust comparisons with non-intervention groups are needed to strengthen evidence for clinical practice and public policies.